Pakistan : Joint Staff Assessment of Poverty Reduction Strategy Paper Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
The paper presents a Joint Staff Assessment (JSA) of the Interim Poverty Reduction Strategy Paper (I-PRSP) Progress Report for Pakistan. The JSA identified some important gaps in the poverty reduction strategy for Pakistan. These include a detailed rural development strategy; a more focused human development strategy; costing of programs to achieve targets, particularly in the health and education sector; and a monitoring framework. The preparation status report emphasizes the government's commitment to continuity of the reforms envisaged in the I-PRSP and outlines various aspects of the process, timeline, content, and progress along these dimensions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: CR; Government; ISCR; PRSP Preparation Status Report; PRSP Secretariat; Pakistan